2001
DOI: 10.1104/pp.126.1.188
|View full text |Cite
|
Sign up to set email alerts
|

A Biophysical Analysis of Stem and Root Diameter Variations in Woody Plants

Abstract: A comprehensive model of stem and root diameter variation was developed. The stem (or root) was represented using two coaxial cylinders corresponding with the mature xylem and the extensible tissues. The extensible tissues were assumed to behave as a single cell separated from the mature xylem by a virtual membrane. The mature xylem and the extensible tissues are able to dilate with temperature and grow. Moreover, the extensible tissues are able to shrink and swell according to water flow intensity. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 42 publications
6
110
0
9
Order By: Relevance
“…The higher variability of MDTS could be explained by different water conductivities in the xylem tissue that are independent of the plant water status (Naor and Cohen, 2003). Xylem water potential is the main driving force of trunk diameter changes (Klepper et al, 1971) but its amplitude is modulated by several factors including the elastic and water diffusion properties of the phloem tissue (Parlange et al, 1975;Génard et al, 2001), bark-xylem osmotic pressure gradients (Cochard et al, 2001), and different organs growth rates (McBurney and Costigan, 1984). In addition, the fact that dendrometers measure the radius in a small region in the trunk and that SWP is representative of a whole branch, may also explain why SWP is less variable than MDTS (Fereres and Goldhamer, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The higher variability of MDTS could be explained by different water conductivities in the xylem tissue that are independent of the plant water status (Naor and Cohen, 2003). Xylem water potential is the main driving force of trunk diameter changes (Klepper et al, 1971) but its amplitude is modulated by several factors including the elastic and water diffusion properties of the phloem tissue (Parlange et al, 1975;Génard et al, 2001), bark-xylem osmotic pressure gradients (Cochard et al, 2001), and different organs growth rates (McBurney and Costigan, 1984). In addition, the fact that dendrometers measure the radius in a small region in the trunk and that SWP is representative of a whole branch, may also explain why SWP is less variable than MDTS (Fereres and Goldhamer, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Calibration showed a decrease in ε 0 , the proportionality constant between the elastic modulus ε and the product of stem diameter and pressure potential (Génard et al, 2001) across the growing season (results not shown). This contrasts with the decrease in elasticity when tissues age.…”
Section: Evolution Of Model Parametersmentioning
confidence: 99%
“…Diurnal patterns of shrinkage and a portion of the subsequent expansion in the stems of trees are caused by variations in tree water relations (Fritts 1976;Kozlowski and Winget 1964). However, much of the daily stem expansion, which can be considered true growth, is a result of cell division and expansion in the cambial zone and the zone of differentiating xylem (Downes et al 2000;Steppe et al 2005).…”
Section: Introductionmentioning
confidence: 98%